Social representations elaborated by nurses about climacteric women in primary health care - Smithanny Barros da Silva; Inez Sampaio Nery; Ayla Maria Calixto de Carvalho (Universidade Federal do Ceará, 2016)
Objective: to understand the social representations elaborated by nurses from the family health strategy concerning the assistance to climacteric women. Methods: qualitative research conducted with 28 nurses. One adopted the reference of procedural approach of the theory of social representations. The interviews were recorded and transcribed completely and processed by the Software of Lexical Analysis of co-occurrence in simple statements of a text, version 4.7. Results: nurses recognize the menopause as a phase of women's life that needs to be assisted in its entirety, however, they showed difficulty in helping them, as they just carry out the cytological examination collection, request laboratory tests and forward them to a doctor. Conclusion: the climacteric period is a multifaceted phenomenon and the assistance to those people should be systematized from a qualified listening, in an approach that respects its uniqueness and autonomy.